2019
DOI: 10.1080/13549839.2019.1572728
|View full text |Cite
|
Sign up to set email alerts
|

A case for urban liveability from below: exploring the politics of water and land access for greater liveability in Kampala, Uganda

Abstract: Improving urban liveability and prosperity is commonly set as a priority in urban development plans and policy around the world. Several annual reports produced by international consulting firms, media, and global agencies rank the liveability of cities based on a set of indicators, to represent the quality of life in these cities. The higher is the ranking, the more liveable is the city. In this paper, we argue that such quantitative approaches to framing and addressing urban liveability challenges leave litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…This growth appears to mount enormous pressure on both localand urban authorities to provide essential services as well as spur the muchneeded development objectives of the urbanizing population. A few of the challenges identified include unsustainable water supply, sanitation and hygiene (Bishoge, 2021), urban liveability and prosperity (Nastar, Isoke, Kulabako, & Silvestri, 2019), urban slump, the explosion of slums, dilapidated housing, and the denationalization of urban growth lacking public greeneries and transport plans (Bolleter et al, 2022), non-communicable diseases (Mackay, 2022), and water pollution (Okurut, Kulabako, Chenoweth, & Charles, 2015), to mention just a few. Even though the country's level of urban sprawl is moderately low, with just 18% of its populace living in cities and towns, it is one of the most rapidly urbanizing countries in Africa.…”
Section: The Context Of Cdfs In Ugandamentioning
confidence: 99%
“…This growth appears to mount enormous pressure on both localand urban authorities to provide essential services as well as spur the muchneeded development objectives of the urbanizing population. A few of the challenges identified include unsustainable water supply, sanitation and hygiene (Bishoge, 2021), urban liveability and prosperity (Nastar, Isoke, Kulabako, & Silvestri, 2019), urban slump, the explosion of slums, dilapidated housing, and the denationalization of urban growth lacking public greeneries and transport plans (Bolleter et al, 2022), non-communicable diseases (Mackay, 2022), and water pollution (Okurut, Kulabako, Chenoweth, & Charles, 2015), to mention just a few. Even though the country's level of urban sprawl is moderately low, with just 18% of its populace living in cities and towns, it is one of the most rapidly urbanizing countries in Africa.…”
Section: The Context Of Cdfs In Ugandamentioning
confidence: 99%
“…Unprotected springs are prone to contamination from surface runoff, animal and bird droppings including all kinds of human waste. For instance, residents in Kampala, Uganda reported that water from unprotected springs was 'very dirty' (Nastar et al 2019). In a related study of water quality in Lukaya, a small town in Uganda unprotected springs demonstrated gross faecal contamination (Nayebare et al 2020).…”
Section: Water Source Typementioning
confidence: 99%
“…In Kampala, Uganda, groundwater is an important part of the urban water cycle, not only for water supply (Flynn et al 2012;Howard et al 2003;Kulabako et al 2007Kulabako et al , 2008Kulabako et al , 2010Nabasirye et al 2011;Nastar et al 2019;Silvestri et al 2018), but also in relation to on-site sanitation and wastewater infiltration to groundwater (Fuhrimann et al 2016;Katukiza et al 2015;Katukiza et al 2014;Lutterodt et al 2014;Lutterodt et al 2012;Ronoh et al 2020;Sakomoto et al 2020;Tumwebaze et al 2019), and groundwater input to wetlands in and around the city (e.g. Kansiime et al 2007;Kyambadde et al 2004;Nyenje et al 2014a;Were et al 2021Were et al , 2020.…”
Section: Introductionmentioning
confidence: 99%